(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
The aim of the present study was the assessment of soil pollution by some potentially toxic trace elements in the environs of Akhtala Mining and Processing Enterprise and related environmental risks. The study was implemented in 2018. The level of soil contamination with trace elements was assessed by Enrichment factor, which is widely used as a contamination index. The study revealed that the soils, almost in all studied sites, were polluted by Cu, Pb, Zn, Co and Ni. From all trace elements studied the highest contents compared with background were observed for copper. Such situation is conditioned by anthropogenic factor, in particular, by mining activities since copper is the main metal extracted in Akhtala Mining and Processing Enterprise.